Solidago chilensis Meyen (Asteraceae), a medicinal plant from South America. A comprehensive review: ethnomedicinal uses, phytochemistry and bioactivity - Gastaldi, Bruno (2018)
Solidago chilensis Meyen (Asteraceae) is a medicinal and aromatic herb widely distributed in South America. From 2000 to the present numerous articles on this species have been published, mainly in the last decade where the pharmacological studies and articles on its secondary metabolites have risen sharply. S. chilensis has potential beneficial effects on human health, particularly as an anti-inflammatory because of its high flavonoid content. This work describes the research carried out on this species with emphasis on biological and phytochemical studies.